Age-related hair changes in men: Mechanisms and management of alopecia and graying. Issue 1 (January 2015) - Mirmirani, Paradi
Highlights Androgenetic alopecia and senescent alopecia are the two main causes of thinning in men. In androgenetic alopecia, hormonal signals lead to changes in genes regulating hair follicle size and cycling and there is a gradual diminution of the hair follicle. In senescent alopecia, which has its onset after the age of 60, follicular dropout and thinning occur as a results of apoptosis and oxidative stress responses and may be a manifestation of systemic aging processes. Extrinsic factors such as hair processing, ultraviolet light, and smoking have a deleterious effect on the hair. Hair graying may reflect a decreased ability to handle oxidative damage as well as loss of follicular melanocytes and melanin content.